2015
DOI: 10.1016/j.neuropharm.2015.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine blocks exercise effects on Bdnf and Drd2 gene expression in frontal cortex and striatum

Abstract: Exposure to drugs of abuse can produce many neurobiological changes which may lead to increased valuation of rewards and decreased sensitivity to their costs. Many of these behavioral alterations are associated with activity of D2-expressing medium spiny neurons in the striatum. Additionally, Bdnf in the striatum has been shown to play a role in flexible reward-seeking behavior. Given that voluntary aerobic exercise can affect the expression of these proteins in healthy subjects, and that exercise has shown pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Rats were pretreated with d -methamphetamine hydrochloride (Sigma, St. Louis, MO), using a subchronic escalating regimen (Thompson et al 2015) that is known to protect DA systems from neurotoxicity following subsequent binge exposures (Segal et al 2003). In experiment 1, rats were given three daily injections (separated by 3.25 h) of methamphetamine (“mAMPH”, n = 11; 0.1–6.0 mg free base/kg, s.c., escalating in 0.1 mg/kg increments up to 2.1 mg/kg, then in 0.2 mg/kg increments from 2.1 mg/kg to 6.0 mg/kg) or physiological saline solution (“SAL”, n = 12; 1 ml/kg, s.c.) for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were pretreated with d -methamphetamine hydrochloride (Sigma, St. Louis, MO), using a subchronic escalating regimen (Thompson et al 2015) that is known to protect DA systems from neurotoxicity following subsequent binge exposures (Segal et al 2003). In experiment 1, rats were given three daily injections (separated by 3.25 h) of methamphetamine (“mAMPH”, n = 11; 0.1–6.0 mg free base/kg, s.c., escalating in 0.1 mg/kg increments up to 2.1 mg/kg, then in 0.2 mg/kg increments from 2.1 mg/kg to 6.0 mg/kg) or physiological saline solution (“SAL”, n = 12; 1 ml/kg, s.c.) for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that rats, when assessed after acute methamphetamine withdrawal, are more willing to expend effort for valued natural rewards such as food and exercise (Stolyarova et al 2015; Thompson et al 2015). Similarly, rats exposed to and withdrawn from a variety of drugs, including the psychostimulants amphetamine, MDMA, and cocaine, show increased lever pressing behavior for sucrose pellets in a progressive ratio task relative to saline-treated animals (Olausson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Experience with reward events may calibrate the impact of subsequent events on D2 receptor signaling; events that may be negative or suboptimal by comparison, as in the case of acute drug-withdrawal (Thompson et al, 2015a). More generally, this role is consistent with the idea that dopamine tone scales the performance of previously learned behavior and that poor reward conditions, as experienced in early reversal learning, are characterized by weaker dopamine signaling, co-occurring with D2 receptor activation (Cagniard et al, 2006, Calabresi et al, 2007).…”
Section: Neurochemical Modulation Of Reversalmentioning
confidence: 99%
“…However, prior exercise in running wheels provided no protection against METH‐induced damage to striatal DA terminals in male rats . Changes in BDNF levels are also associated to reward‐seeking behavior . Hilburn et al newly found that serum BDNF levels in METH‐dependent humans were related to the number of abstinent days since last abuse, but not related to craving and substance use history.…”
Section: Neurobiology Of Exercise On Meth Addiction Managementmentioning
confidence: 99%
“…Voluntary aerobic exercise (wheel running) increases BDNF exon IV transcription in rat hippocampus . However, METH exposure prior to initiation of aerobic exercise (6 weeks of voluntary wheel running) prevented the increases in both cortical and striatal BDNF seen in saline‐treated animals that exercised . The impact of physical exercise on BDNF levels in METH addicts warrants further evaluation because it was recently demonstrated that patients with serum BDNF levels ≤1251.0 pg/mL had higher risk of depression symptoms during METH withdrawal .…”
Section: Neurobiology Of Exercise On Meth Addiction Managementmentioning
confidence: 99%